CIVIL SOCIETY AND POST-CONFLICT LIBERIA AND SIERRA LEONE – INSIGHTS FROM DISCOURSE THEORY - OPRIȘ, Lavinia-Ioana (Studia Universitatis Babes-Bolyai Studia Europaea, 2015)
The aim of this article is to analyse civil society in the context of post-conflict Liberia and Sierra Leone through the lens provided by discourse theory as coagulated in the works of Ernesto Laclau and Chantal Mouffe. It is our contention that external interventions by donors were guided by a hegemonic articulation which envisaged civil society as a clearly defined moment in a discourse which equated reconstruction with development and good governance. In addition to mapping some of the consequences of the aforementioned hegemonic discursive articulation, we also plan to use the proposed framework to determine whether this articulation has been fully dislocated.